Culture, industrialisation and multiple domains of employees' job satisfaction: a case for HR strategy redesign in India - Lange, Thomas; Pacheco, G.; Shrotryia, V. (Routledge, 2010)
This paper explores the link between cultural behavioural traits, the potential effect of industrialisation and multiple domains of job satisfaction, utilising survey data collected from public and private service sector employees in Shillong, the capital city of Meghalaya in the North East Region (NER) of India. Results from ordered probit regressions demonstrate a statistically significant impact of both, extrinsic and intrinsic moderating factors on Indian employees' job satisfaction. In view of India's widely reported collectivistic cultural traits, which are assumed to emphasise primarily the importance of extrinsic job aspects, our findings are surprising. They suggest that in the wake of India's significant economic developments the impact of intrinsic job rewards has played ‘catch-up’ with that of their extrinsic counterparts. As such, the study provides evidence in support of embracing human resource management (HRM) practices that incentivise Indian employees not only through their traditional methods aimed at extrinsic job rewards but also by explicitly addressing individual ambitions, needs and aspirations.